Penyusunan Spesimen Awetan Tumbuhan dan Hewan Di SMPN 20 Mataram - I Putu Artayasa; Muhlis Muhlis; Agus Ramdani (Jurnal Pengabdian Masyarakat Sains Indonesia, 2021)
Abstract: The Biology Science Practicum has a role in improving the quality of science learning, especially Biology material, as well as improving science process skills and students' understanding of science concepts. The Biology Science Practicum requires the availability of plant and animal specimens as the main object of observation, but this is not widely available in the Science Laboratory of SMPN 20 Mataram, thus causing the Biology Science practicum not to be carried out properly. The purpose of this community service is to increase the understanding and skills of teachers to make specimens of preserved plants and animals. The method of implementing community service was to provide training for teachers to make specimens of preserved plants and animals which was conducted in September 2020. The training was guided by lecturers, education staff (laboratory assistants), and students. Questionnaires were given to training participants to evaluate the effectiveness of community service programs. The result of the training was that there were twenty teachers who came from science teachers and other subjects involved in training in making insectariums, herbariums, Mollusca shell preserves, and animal wet preserves, and participants responded that the training had increased the knowledge and skills of teachers in making plant specimens and animal. The conclusion is that the training carried out by providing samples of preserved specimens of living things, demonstrations and assistance in making preserved specimens have an impact on increasing participants' understanding and skills in making preserved specimens of plants and animals. Keywords: Dry and wet preservation of living things; Herbarium; insectarium; Biology practicum; Plant and animal specimens.